2017
DOI: 10.1099/jgv.0.000757
|View full text |Cite
|
Sign up to set email alerts
|

ICTV Virus Taxonomy Profile: Iflaviridae

Abstract: Iflaviridae is a family of small non-enveloped viruses with monopartite, positive-stranded RNA genomes of approximately 9–11 kilobases. Viruses of all classified species infect arthropod hosts, with the majority infecting insects. Both beneficial and pest insects serve as hosts, and infections can be symptomless (Nilaparvatalugens honeydew virus 1) or cause developmental abnormalities (deformed wing virus), behavioural changes (sacbrood virus) and premature mortality (infectious flacherie virus). The host ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 4 publications
4
121
0
Order By: Relevance
“…The synergistic interaction between V. destructor and DWV is one of the major threats to the honey bee industry (Di Prisco et al 2016). DWV belongs to the Iflaviridae family (Valles et al 2017) so it is also a +ssRNA virus, like the new viruses described here. Therefore, it is possible that its replication and transmission of DWV in the mites could be influenced by the presence of other viruses from the same family (VdIV-2) or with similar replication mechanism (VdV-3 and VdV-5).…”
Section: Interaction Of the New Viruses With Dwvmentioning
confidence: 80%
See 1 more Smart Citation
“…The synergistic interaction between V. destructor and DWV is one of the major threats to the honey bee industry (Di Prisco et al 2016). DWV belongs to the Iflaviridae family (Valles et al 2017) so it is also a +ssRNA virus, like the new viruses described here. Therefore, it is possible that its replication and transmission of DWV in the mites could be influenced by the presence of other viruses from the same family (VdIV-2) or with similar replication mechanism (VdV-3 and VdV-5).…”
Section: Interaction Of the New Viruses With Dwvmentioning
confidence: 80%
“…The genome of the VdIV-2 UK contains a single large ORF, that translates into 2996 amino acids polyprotein, displaying the characteristic Iflaviridae structure organisation (Valles et al 2017) (Fig 1B). Conserved motifs for the Non-structural proteins, RdRp, 3C-like cysteine protease and RNA helicase, were detected in the C-terminal region of the polyprotein.…”
Section: New Viruses Associated To V Destructormentioning
confidence: 99%
“…DWV is the major virus pathogen of honey bees and is associated with increased colony losses worldwide that have affected pollination services and food security [23,24]. DWV belongs to the family Iflaviridae (order Picornavirales) which includes 15 recognized and 18 pending virus species infecting a wide range of insects [21]. It is very likely that the real diversity and distribution of this virus group is much wider and therefore it is likely to have a great impact on many invertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…Members of three positive-sense single-stranded RNA virus families such as Dicistroviridae (Bonning and Miller, 2010), Iflaviridae (Valles et al, 2017) and Picornaviridae (Zell, 2018) are widely reported from insects. These families were included in a new virus order Picornavirales (Le Gall et al, 2008).…”
mentioning
confidence: 99%
“…Several members of these insect small RNA virus families cause clear signs of disease in their hosts, such as infectious flacherie virus in silkworms (Valles et al, 2017), and deformed wing virus (Wilfert et al, 2016) and slow bee paralysis virus in honeybees (Bonning and Miller, 2010). It has been suggested that the picorna-like viruses or other members of Picornavirales can be maintained in insects by horizontal and vertical transmission .…”
mentioning
confidence: 99%